Readiness for and predictors of evidence-based practice of acute-care nurses: a cross-sectional postal survey. - Thorsteinsson, Hrund S.; Sveinsdóttir, Herdís (Scandinavian Journal of Caring Sciences, 2014)
Background Nurses' adoption of evidence-based practice ( EBP) remains limited although most nurses are familiar with EBP and belief in its value for patient care. Efforts to accelerate nurses' EBP activities have met with limited success. Knowledge of predictors of nurses' EBP activities is lacking. Aims To describe nurses' readiness for EBP as measured by their information needs, skills in using electronic bibliographical databases ( EBDs) and awareness of available EBP-needed resources; EBP beliefs and frequency of EBP activities, and identify predictors of EBP activities and beliefs. Methods This was a cross-sectional survey, distributed to a homogeneous, consecutive sample of 546 acute-care nurses. Response rate was 64.3%; responses from direct-care nurses (n = 298) and administrators (n = 45) were analysed. Descriptive statistics were used to describe readiness for EBP, frequency of certain EBP activities and EBP beliefs. Logistic regression analyses were performed to identify predictors of EBP activities and multiple regression analysis to identify predictors of EBP beliefs. Results The nurses generally seldom participated in the EBP activities studied, in spite of familiarity with and positive beliefs towards EBP. Evidence-based practice beliefs predicted all three activities studied. Skills in using EBDs predicted information-seeking and evaluating research. Awareness of available EBP-needed resources predicted information-seeking, role predicted evaluating research, while familiarity with EBP predicted using research in practice. Six predictors explained nearly 40% of the variance in EBP beliefs. Conclusions Nurses' EBP activities must be facilitated and accelerated. The findings provide empirical support to the primacy of EBP beliefs in nurses' engagement in EBP and of the complexity of EBP. While the identified predictors of EBP activities and beliefs are susceptible to change, diverse strategies are needed to influence each one. Strategies should focus on influencing EBP beliefs, that is, by increasing skills in using EBDs, discussion about EBP in the clinical environment and familiarity with EBP.